Edukasi Literasi Keuangan: Investasi pada Emas, Urgensi Dana Darurat, dan Pengendalian Gaya Hidup Konsumtif - yusuf, keona adeline; Polandauw, Clarissa Amanda; Jocelyn, Angelique; Linawati, Nanik (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
Low financial literacy amongst the younger generation can hinder the economic growth of a developing country. The lack of knowledge about basic financial concepts and financial instruments is caused by the scarcity of educational curriculum related to financial literacy. The lack of an educational curriculum related to financial literacy makes education related to crucial. This community service is motivated by the urgency of improving the financial literacy of junior high school students and aims to form a foundation for good financial behavior. The educational material provided is relevant and easy to understand for junior high school students. The material is provided using interactive presentation media accompanied by educational games that are specifically designed with the sub-topics "Investing in Gold", "Emergency Funds", and "Consumptive within Your Limits". Education and games help students understand the basic concepts of finance and their applications in real life. After the community service activities, students showed an increase in understanding of basic financial concepts, this can be seen from their enthusiasm and high average test scores.